Karin Alvtegen as researcher of "ongoing suffering": cultural analysis - N. A. Zhukova (Ukrainian Cultural Studies, 2018)
The article deals with the cultural analysis of the novels "Shame" and "Betrayal" by the famous contemporary Swedish writer Karin Alvtegen, which are an example of a new art that has replaced the art of "post". "New art" is expressed in the return to the subject-object coherence, the reflection of reality in holistic, specifically-sensual artistic and expressive forms. The novel "Shame" is a psychological thriller where the author tells about the fate of three women - Monica, May-Britt and Vanya Turin. All three of them (independently) feel ashamed for their whole lives because of the events they had experienced during their childhood or youth, and this feeling, in its turn, influenced their behavior, and determined the subsequent attitude to people and life. In Alvtegen’s novel "Betrayal" she describes the psychological state of all the heroes, who, as it turns out, are both victims of betrayal and the traitors. Simultaneously, the author develops the topic of devastating revenge and the dilemma of forgiveness-non-forgiveness. In the end, the author inclines to the first variant, which helps to overcome a psychological trauma - "a trauma of betrayal". For the heroes of Alvtegen, betrayal and vengeance are the phenomena of the same tier, and both bring unbearable mental pain, and all characters have a constant internal dialogue with it. "Trauma of betrayal" rules over the author’s characters, who do not realize what drives them. According to Sigmund Freud, this trauma separates a person from the surrounding reality, closes him/her on itself, and, at some point, brings satisfaction. However, if Freud’s "trauma" is constructive even in case its consequences are abnormal, the damage it caused is compensated, even though in a neurotic way. Yet, for the heroes of Alvtegen, the trauma takes away human ability to act, induces a negative belief in oneself or in others, and, at the same time, it is a trial given to a person, a kind of initiation. None of the characters of the Swedish writer can pass this initiation. As a result, the lives of all characters are ruined. Hence, having appeared in the world due to the trauma of birth (according to O. Rank), experiencing various types of traumas during life (S. Freud, C.G. Jung, A. Adler, S. Spielrein, J. Lacan), the vector of behavior depends on a person. The novels by Alvtegen showed the tendency to combine the problems of fundamental ontology, psychoanalysis, and the idea of "integral humanism" in the new art ("proto-art") as a way to escape the "ongoing suffering." It is noted that the novels by Alvtegen are a complicated, aesthetically organized system of meanings that involve "multiple coding", organic interweaving of psychoanalytic ideas, in particular, the phenomenon of "trauma" into the concept of the M. Heidegger fundamental ontology.
Keywords: Dasein, shame, fear, betrayal, trauma, suffering, caring, "integral humanism", "proto-art"